Tradition and modernity in Iran art based on visual arts - Shahrzad Salehipour (پیکره, 2013)
One of the dimensions of modernity manifestation in Iran is the field of visual art, which among its evident aspects there isselective use without considering the basis ofreasoning and contemplation of western thought and modernity. In order to clarify several concepts of modernity and tradition existing in the realm of thought, the necessity of more detailed and accurate assessment of tradition is very essential. Therefore, with more knowledge and information of thought structure in our culture and its differences with western culture, we will achieve a more precise recognition of it. The first section of this study is searching the nature of tradition, how dynamic it is and assessing the main origin of modernity.In this section, different theories of conflict and coexistence of them in contemporary sociology and anthropology are included as well. Also with the theory of Georges Balandier in the issue of multiplicity of modernity, the possibility of realization of a modernity different from that of western experience as a possible experience for surrounding societies, is taken into account. In the second section, through study of how tradition and modernity exist in Iran, the current position of tradition and modernity in Iran is presented by providing views of experts. In the third section, via presenting the current condition of tradition and modernity in visual arts of Iran, existing problems in the education of art are considered; at the end by taking into account the fact that in the area of contemplation and thought, it is the raising of question that is clarifying not providing the answer, certain questions are raised in order to present suitable solutions.